2013
DOI: 10.1016/j.ijid.2013.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus core protein induces hepatic metabolism disorders through down-regulation of the SIRT1–AMPK signaling pathway

Abstract: HCV core protein induces alterations in cellular redox state (decrease in the NAD(+)/NADH ratio), which could influence the activity of SIRT1 and secondarily AMPK, then change the expression profile of glucose and lipid metabolism-related genes, thereby causing metabolism disorders of hepatocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 23 publications
3
44
0
Order By: Relevance
“…The modulation of AMPK has been studied during the infection with other viruses such as hepatitis C virus (HCV), where it was observed the inhibition of this kinase and the concomitant intracellular lipids accumulation [5254]. As well, the latent membrane protein 1 from Epstein-Bar virus (EBV) inhibits the AMPK activity and the subsequent downstream effectors activation [55].…”
Section: Discussionmentioning
confidence: 99%
“…The modulation of AMPK has been studied during the infection with other viruses such as hepatitis C virus (HCV), where it was observed the inhibition of this kinase and the concomitant intracellular lipids accumulation [5254]. As well, the latent membrane protein 1 from Epstein-Bar virus (EBV) inhibits the AMPK activity and the subsequent downstream effectors activation [55].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, lipid droplets become inaccessible for cell lipases. In addition, CP regulates the expression of protein factors of lipid metabolism [276279]. Integral action of CP increases the number of lipid droplets and induces their fusion yielding lipid vacuoles [274].…”
Section: Viral Infectionsmentioning
confidence: 99%
“…As mentioned earlier, AMPK stimulates hepatic fatty acid oxidation and ketogenesis, since it lowers malonyl-CoA liver content, thereby permitting fatty acid transport to the mitochondria, where they suffer oxidation [30] . Ethanol exerts an inhibitory effect on AMPK [54] and HCV also downregulates AMPK [29] . In a study performed on 30 patients infected with HCV it was found that mitochondrial β-oxidation of fatty acids was impaired and that this impairment was related to serum levels of HCV core protein [8] .…”
Section: Inhibition Of Fatty Acid Oxidationmentioning
confidence: 99%
“…Ethanol inhibitis sirtuin-1 activity, therefore increasing the lipogenic effect of SREBP 1-c [26] . HCV exerts a similar effect [29] . Sirtuin activity is coupled to that of AMP-activated kinase (AMPK), an enzyme that phosphorylates and, thus, inhibits, acetyl-CoA carboxylase, interrupting the formation of malonyl-CoA, a key step for fatty acids synthesis, and preserving cellular content in NAD [30] .…”
Section: Inhibition Of Fatty Acid Oxidationmentioning
confidence: 99%